Antimicrobial Activity of Endophytic Fungi Isolated From Fagraea fragrans Roxb. - Insain, Praphaiphit; Boonsom, Teerawat; Pharadai, Kalaya; Sriubolmas, Nongluksna (Journal of Health Sciences and Wellness, 2020)
The aim of this study was to isolate endophytic fungi which produced secondary metabolites from any part of Fagraea fragrans Roxb. Parts of plants sample (leave, bark and cambium) were surface-sterilized and cultured on 6 mycological media including Czapek yeast autolysate agar (CzYA), malt Czapek agar (MCzA), malt extract agar (MEA), potato dextrose agar (PDA), Sabouraud’s dextrose agar (SDA) and yeast extract sucrose agar (YSA) for 14 days. The endophytic fungi were identified based on the microscopic morphology and screened for anti-bacterial and anti-fungi activities by dual culture agar diffusion assay. A total of 24 endophytic fungal isolates were isolated from leaves, bark and cambium of the plant sample. They demonstrated 3 active isolates (12.5%) which showed antimicrobial activities. The isolate Ffra L24 was found to inhibit methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E.coli). The Isolates Ffra B14 and Ffra B15 exhibited synergistic activity with ketoconazole against Candida albicans. The type of culture media affected the bioactive compounds production of endophytic fungi. CzYA, MCzA and YSA were suitable for endophytic fungi to produce bioactive compounds. Classification of Ffra B14, Ffra B15 and Ffra L24 based on the microscopic morphology suggested that they were Coelomycetes.